Peranan Penataan Kearsipan Sebagai Sumber Informasi Bagi Pimpinan Dalam Pengambilan Keputusan - Christina, Rina; Asmara, Nefi Aris Ambar (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2010)
In every organization, has several functions which are connected each others in term of support for the whole organization goals. The most important organizational beside resources human resource is the information, with those information it s able to support the decision making addressed to the top manager. In this case, the information resources can be found among the archives. In the condition that the archives should be manage as well as possible and with the archive’s managerial manner including: collecting, processing, technically maintaining, classification, recording, filling and retrieval sistem